OPTIMASI SISTEM INFORMASI PENGELOLAAN DATA KESEHATAN PEGAWAI PADA UNIT P3K PT KEBON AGUNG PG TRANGKIL MENGGUNAKAN METODE AGILE DENGAN PENDEKATAN SCRUM - Rahmawati, Yulinda; Setiawan, R. Rhoedy; Irawan, Yudie; Setiaji, Pratomo (LPPM Universitas Putera Batam, 2025)
This study is entitled “Optimization of Employee Health Data Management Information System at P3K Unit PT Keon Agung PG Trangkil Using Agile Method with Scrum Approach”. This study aims todevelop an integrated and flexible informastions system to manage employee healrt data. With agile method with Scrum approach, the system is developed in stages through Sprint, adjusted ased on user feedback. The system is designed to record examination data, classify results into mild and severe diseases, and process referrals for severe disease cases. The development results show increased efficiency, accuracy of recording, and support management in making decisions related to employee welfare